Enrichment of whole grain bread with herbal additives - Bazhay-Zhezherun, Svitlana; Bereza-Kindzerska, Ludmyla; Bashta (Sheremet), Alla; Fedorenko, Tetiana (My University, 2024)
A comparative assessment of the chemical composition of whole grain and hemp flour was carried out. We investigated the organoleptic parameters of sweet potato fruits and puree from it, as well as the chemical composition of the specified raw materials. We researched the influence of hemp flour and sweet potato puree on physico-chemical quality indicators of dough and whole grain bread. The dough was kneaded using a steamless method from wheat whole-grain flour with the addition of hemp flour in an amount of 4-10% and sweet potato puree – 2-8 %. Enrichment of whole wheat bread with hemp flour and sweet potato puree does not impair the porosity structure of products. If hemp flour is added in an amount of 4-8%, and sweet potato puree in an amount of 2-6%, the taste and aroma remain not only acceptable, but also acquire a pleasant light shade of enrichers. Whole grain bread enriched with hemp flour and sweet potato puree is a functional food product. It was found that the degree of provision of daily demand for macro- and micronutrients, adult population of the first group of intensity, due to the consumption of 100 g of whole grain bread enriched with hemp flour is: proteins – 15 %, fats – 3.1 %, carbohydrates – 15.6 %, dietary fiber – 11 %; vitamins: E – 18 %, β -carotene – 11.5 %, B1 – 17 %, B2 – 5.8 %. A comparative assessment of the chemical composition of whole grain and hemp flour was carried out. We investigated the organoleptic parameters of sweet potato fruits and puree from it, as well as the chemical composition of the specified raw materials. We researched the influence of hemp flour and sweet potato puree on physico-chemical quality indicators of dough and whole grain bread. The dough was kneaded using a steamless method from wheat whole-grain flour with the addition of hemp flour in an amount of 4-10% and sweet potato puree – 2-8 %. Enrichment of whole wheat bread with hemp flour and sweet potato puree does not impair the porosity structure of products. If hemp flour is added in an amount of 4-8%, and sweet potato puree in an amount of 2-6%, the taste and aroma remain not only acceptable, but also acquire a pleasant light shade of enrichers. Whole grain bread enriched with hemp flour and sweet potato puree is a functional food product. It was found that the degree of provision of daily demand for macro- and micronutrients, adult population of the first group of intensity, due to the consumption of 100 g of whole grain bread enriched with hemp flour is: proteins – 15 %, fats – 3.1 %, carbohydrates – 15.6 %, dietary fiber – 11 %; vitamins: E – 18 %, β -carotene – 11.5 %, B1 – 17 %, B2 – 5.8 %.
Keywords: whole wheat flour; sweet potato puree; hemp flour; protein; nutritional value; цільнозернове борошно; пюре батату; конопляне борошно; білок; харчова цінність; кафедра технології оздоровчих продуктів